2017
DOI: 10.18203/2320-6012.ijrms20174598
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CD4 and CD8 counts and ratio in HIV negative pulmonary tuberculosis patients with normal healthy controls

Abstract: Background: There is an equivocal contention that Tuberculosis may be a cause of non-HIV-associated CD4+ T cell lymphopenia. In HIV negative patients, CD4+ and CD8+ T cell count suppression has been associated with TB infection. Prediction of HIV coinfection in newly diagnosed pulmonary TB patients with negative HIV status by estimation of CD4, CD8 count and CD4:CD8 ratio.Methods: Newly diagnosed pulmonary TB patients comprising of 30 numbers with negative HIV status were subjected for estimation of CD4, CD8 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Similarly, Uppal et al (12) and Siraj et al (14) also found CD4:CD8 Ratio was lower in patients of pulmonary tuberculosis compared to healthy controls. This finding is contrary to that observed by Sabhapandit et al (13) In our study we also found that mean CD4:CD8 Ratio was lower in pulmonary tuberculosis patients who never had treatment for tuberculosis than in pulmonary tuberculosis patients who have received anti-tuberculosis treatment for more than one month. From our study and previous studies this can be predicted that pulmonary tuberculosis may be responsible for change in CD4:CD8 Ratio.…”
Section: Comparison Of the Variable Subgroups In Terms Of Cd4: Cd8 Ra...contrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, Uppal et al (12) and Siraj et al (14) also found CD4:CD8 Ratio was lower in patients of pulmonary tuberculosis compared to healthy controls. This finding is contrary to that observed by Sabhapandit et al (13) In our study we also found that mean CD4:CD8 Ratio was lower in pulmonary tuberculosis patients who never had treatment for tuberculosis than in pulmonary tuberculosis patients who have received anti-tuberculosis treatment for more than one month. From our study and previous studies this can be predicted that pulmonary tuberculosis may be responsible for change in CD4:CD8 Ratio.…”
Section: Comparison Of the Variable Subgroups In Terms Of Cd4: Cd8 Ra...contrasting
confidence: 99%
“…In our study we found CD4 cell count was lower in HIV negative pulmonary tuberculosis patients than in normal healthy controls. Similarly, Uppal et al (12) , Sabhapandit et al (13) and Siraj et al (14) also found CD4 cell count was lower in patients of pulmonary tuberculosis compared to healthy controls. In our study we also found that mean CD4 cell count was lower in pulmonary tuberculosis patients who never had treatment for tuberculosis than in pulmonary tuberculosis patients who have received anti-tuberculosis treatment for more than one month.…”
Section: Comparison Of the Variable Subgroups In Terms Of Cd4 Count (...mentioning
confidence: 78%
“…Available data on CD8+ T-lymphocytes count in patients with TB are contrasting. In some studies, the CD8 + T-cells count was significantly decreased ( 15 , 16 , 40 , 41 ), while in other studies it was unmodified ( 13 , 15 ) or increased ( 14 , 32 ) compared to healthy controls. In our study, the finding of a significantly decreased CD4+/CD8+ ratio in patients with TB compared to patients with CAP might be explained by assuming both a peripheral depletion of the CD4+ T-cells compartment and an increase in the peripheral CD8+ T-cells population.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, our dedicated ward for respiratory diseases is located in a South Europe country with low TB incidence [in 2020, the incidence of tuberculosis in Italy was 6.6 cases per 100,000 people (49)], which makes it more difficult to collect a large number of patients. However, we were able to collect a number of patients that is comparable with other similar studies on the topic (13,16,17,32,41). Second, the analysis did not include a control group of healthy subjects for comparison.…”
Section: Discussionmentioning
confidence: 98%